Evaluation of teaching methods in pharmacology among MBBS students - Vare, Vijay A.; Kurle, Dynaneshwar G.; Bagle, Tushar R.; Hire, Rohan C.; Shukla, Abhaykumar O. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Pharmacology is one of the most important subjects in medical curriculum. It is basis of medical science and the foundation of treatment. The applied aspect forms the basis of clinical rational therapeutics. Methods: A cross-sectional study among 100 undergraduate medical students was undertaken after Institutional Ethics committee permission. Questionnaire was prepared from previous studies and validated by experts. These were administered to the participants after receiving their due consent. Results: The mean age of students was 21.31±2.93 years. There were 72% females and 28% males. The average rating given for Pharmacology subject was 7.95±1.16. Females (8.38±1.24) rated Pharmacology subject more than males (7.51±1.09). 62% liked combination of LCD and Blackboard for teaching. 34% felt group discussion was the ideal Teaching learning method for learning Pharmacology. The most interesting topic was General Pharmacology (31%) and ANS (45%) was the most difficult subject to understand. The most important topic in practical’s was 25% prescription writing and least was experimental graphs (2%). Preferred source to learn Pharmacology was combination of textbook and lecture (42%). 81% students liked integrated teaching of pharmacology with other subjects. 93% felt there should be more use of audiovisual aids, 91% wanted more of clinical pharmacology and 88% wanted more of group discussions. 91% felt calculation of pharmacokinetic parameters is clinically applicable. Conclusions: There is need to develop innovative teaching learning methods and include more of clinical pharmacology in the undergraduate pharmacology subject.